(untitled) (Journal of Comparative Social Work, 2007)
My colleague and I came to a centre for rights protection of children and adolescents in a city in Northern Russia. It was a winter day with snow all over. In an open space between the houses, just before the entrance to the centre building, we met two eight or nine-year-old girls, skiing. They were smoking cigarettes. My colleague, who is a Russian, said as a joke: “Don’t you know when you smoke a second head will grow on your shoulders?” The answer came right-away: “I don’t care!” This little conversation in Russian was our introduction to a series of meetings with different spokespersons working at arenas with influence on child and adolescent welfare in the region.